Sustainability of the Breastfeeding-Friendly Primary Care Initiative: a cross-sectional study - Rafaele Rosa Febrone; Maria Inês Couto de Oliveira; Rosane Valéria Viana Fonseca Rito; José Rodrigo de Moraes (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to assess the sustainability of the Breastfeeding-Friendly Primary Care Initiative by analyzing compliance with the Ten Steps in accredited units; and association with maternal satisfaction and exclusive breastfeeding. Methods: a cross-sectional study conducted in 2016. An assessment of compliance, conducted by interviews with health professionals, pregnant women, and mothers. An association between compliance and satisfaction, analyzed by Spearman›s correlation test; and association between contextual/individual characteristics and exclusive breastfeeding, by the multilevel Poisson regression. Results: compliance was 5.4-10 points and satisfaction was 36.8%-100%. Prevalence of exclusive breastfeeding was 56.7%. There was a correlation between compliance and satisfaction. Higher education, prenatal orientation, hospital discharge on exclusive breastfeeding, attendance in mixed units, and female gender of the child were associated with higher prevalence of exclusive breastfeeding; on the other hand, increasing age and pacifier use were associated with lower prevalence. Conclusions: the Initiative proved to be sustainable; compliance with the Ten Steps was high and was reflected in maternal satisfaction.